Implementation of Trans Jatim Bus - Eka Nuraini; Bayu Priambodo (Univiversitas Dr. Djar Wattiheluw, 2024)
The Trans Jatim Bus is a Bus Rapid Transit (BRT) that has the power to help people’s mobility quickly, comfortably, and cheaply as a means of public transportation under the auspices of the East Java Provincial Transportation Office. The purpose of this research is to analyze and describe the Implementation of Trans Jatim Bus Use in Sidoarjo, Surabaya, Gresik, and Mojokerto. The research method used is qualitative with a descriptive approach using the theory of Ripley and Franklin (1986) quoted in Purwanto (2015). The data collection techniques used were interviews, observation, and documentation. The data analysis model consists of data collection, data condensation, data display, and conclusion drawing/verifying. The research results that the overall implementation of the use of Trans Jatim Buses was good, many people switched from using private transportation to using Trans Jatim Bus public transportation. It is just that it needs to be improved and developed again regarding the route and service.